Biased μ-opioid receptor agonists diversely regulate lateral mobility and functional coupling of the receptor to its cognate G proteins - Melkes, Barbora; Hejnova, Lucie; Novotny, Jiri (Naunyn-Schmiedeberg's archives of pharmacology, 2016)
There are some indications that biased μ-opioid ligands may diversely affect μ-opioid receptor (MOR) properties. Here, we used confocal fluorescence recovery after photobleaching (FRAP) to study the regulation by different MOR agonists of receptor movement within the plasma membrane of HEK293 cells stably expressing a functional yellow fluorescent protein (YFP)-tagged μ-opioid receptor (MOR-YFP). We found that the lateral mobility of MOR-YFP was increased by (D-Ala2,N-MePhe4,Gly5-ol)-enkephalin (DAMGO) and to a lesser extent also by morphine but decreased by endomorphin-2. Interestingly, cholesterol depletion strongly enhanced the ability of morphine to elevate receptor mobility but significantly reduced or even eliminated the effect of DAMGO and endomorphin-2, respectively. Moreover, the ability of DAMGO and endomorphin-2 to influence MOR-YFP movement was diminished by pertussis toxin treatment. The results obtained by agonist-stimulated [35S]GTPγS binding assays indicated that DAMGO exhibited higher efficacy than morphine and endomorphin-2 did and that the efficacy of DAMGO, contrary to the latter agonists, was enhanced by cholesterol depletion. Overall, our study provides clear evidence that biased MOR agonists diversely affect receptor mobility in plasma membranes as well as MOR/G protein coupling and that the regulatory effect of different ligands depends on the membrane cholesterol content. These findings help to delineate the fundamental properties of MOR regarding their interaction with biased MOR ligands and cognate G proteins.
Keywords: GTP-Binding Protein alpha Subunits, Gi-Go; Oligopeptides; Luminescent Proteins; vztah mezi dávkou a účinkem léčiva; cholesterol; narkotika - antagonisté; Morphine; FRAP; HEK293 Cells; Recombinant Fusion Proteins; bakteriální proteiny; transfekce; Bacterial Proteins; Transfection; rekombinantní fúzní proteiny; guanosin 5'-O-(3-thiotrifosfát); lidé; Narcotic Antagonists; Protein Transport; proteiny vázající GTP - alfa-podjednotky Gi-Go; oligopeptidy; G protein coupling; Enkephalin, Ala(2)-MePhe(4)-Gly(5)-; HEK293 buňky; Cholesterol; Ligands; transport proteinů; Receptors, Opioid, mu; Dose-Response Relationship, Drug; luminescentní proteiny; μ-Opioid receptor; Guanosine 5'-O-(3-Thiotriphosphate); Pertussis Toxin; Fluorescence Recovery After Photobleaching; receptory opiátové mu; morfin; pertusový toxin; Microscopy, Confocal; konfokální mikroskopie; Biased agonists; buněčná membrána; enkefalin, Ala(2)-MePhe(4)-Gly(5)-; ligandy; Cell Membrane; Humans